If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(1 + x) + 2x = -1x + 1 x + (1 * -1 + x * -1) + 2x = -1x + 1 x + (-1 + -1x) + 2x = -1x + 1 Reorder the terms: -1 + x + -1x + 2x = -1x + 1 Combine like terms: x + -1x = 0 -1 + 0 + 2x = -1x + 1 -1 + 2x = -1x + 1 Reorder the terms: -1 + 2x = 1 + -1x Solving -1 + 2x = 1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -1 + 2x + x = 1 + -1x + x Combine like terms: 2x + x = 3x -1 + 3x = 1 + -1x + x Combine like terms: -1x + x = 0 -1 + 3x = 1 + 0 -1 + 3x = 1 Add '1' to each side of the equation. -1 + 1 + 3x = 1 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = 1 + 1 3x = 1 + 1 Combine like terms: 1 + 1 = 2 3x = 2 Divide each side by '3'. x = 0.6666666667 Simplifying x = 0.6666666667
| -11.1=8.1+v/6 | | 375=900-300p | | 2-sec^2(X)=2tan^2(X) | | T/8=13 | | 4x-6*-2=15 | | W^2-6w-66=0 | | 2log(x-1)=5log(y+2) | | (4*5)/5+4=c | | logx+3logy=0 | | 5*4/5+4 | | (10n+10)-10=10 | | 3*-4-6/x=12 | | X^4+4.33X^3-10.34X^2-54.35X-51.67=0 | | 10n+10-10=10 | | 4s-3t=Ifors | | -2x+3x=-15 | | w(3w+2)-2(w^2-8)=w(w+5)-6w+7 | | H+3/4=78 | | 3x^2+x=-11x | | 6/x=3/5 | | 5+2*x=2*x+5 | | 5+2*x=5+(2x) | | T+5=23 | | 8d+b/2b+2d | | 5+2*x=(5-2)x | | 2p^2+2=6p | | 2x+0,1-4*(1-4x)=8x-4,4 | | 14x+47=23 | | (4x+1)(3x-6)=0 | | 5+2*x=7x | | (4+5x)-3*(2-x)=16x-0,4 | | (3x+6)(2x+8)=0 |